STING Signaling and Sterile Inflammation - Couillin, Isabelle; Riteau, Nicolas (Frontiers in Immunology, 2021)
Innate immunity is regulated by a broad set of evolutionary conserved receptors to finely probe the local environment and maintain host integrity. Besides pathogen recognition through conserved motifs, several of these receptors also sense aberrant or misplaced self-molecules as a sign of perturbed homeostasis. Among them, self-nucleic acid sensing by the cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING) pathway alerts on the presence of both exogenous and endogenous DNA in the cytoplasm. We review recent literature demonstrating that self-nucleic acid detection through the STING pathway is central to numerous processes, from cell physiology to sterile injury, auto-immunity and cancer. We address the role of STING in autoimmune diseases linked to dysfunctional DNAse or related to mutations in DNA sensing pathways. We expose the role of the cGAS/STING pathway in inflammatory diseases, neurodegenerative conditions and cancer. Connections between STING in various cell processes, including autophagy and cell death, are developed. Finally, we review proposed mechanisms to explain the sources of cytoplasmic DNA.